Osseointegration. Issue 4 (December 2021) - Sabharwal, Samir; Shores, Jaimie T.; Forsberg, Jonathan A.
Abstract : Osseointegration is a technique that confers a number of advantages to amputees dissatisfied with traditional socket prostheses. An osseointegrated implant consists of a bone-anchored device attached to a patient's residual limb, and a transdermal component, which connects the external prosthesis. By anchoring into bone, an osseointegrated prosthesis provides direct skeletal attachment, allowing for improved mobility and coordination, gait which more closely approximates a native limb, better proprioception, and obviation of the problems associated with the traditional socket—residuum interface, including poor socket fit and soft tissue irritation. Both the bony and soft tissue work of osseointegration warrant careful consideration. We recommend collaboration between rehabilitation, orthopedic, and plastic surgery teams at each step of the process.